2015
DOI: 10.1038/nnano.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emitters in exfoliated WSe2 structures

Abstract: Crystal structure imperfections in solids often act as efficient carrier trapping centres, which, when suitably isolated, act as sources of single photon emission. The best known examples of such attractive imperfections are well-width or composition fluctuations in semiconductor heterostructures (resulting in the formation of quantum dots) and coloured centres in wide-bandgap materials such as diamond. In the recently investigated thin films of layered compounds, the crystal imperfections may logically be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

59
815
9
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 771 publications
(887 citation statements)
references
References 22 publications
59
815
9
4
Order By: Relevance
“…Our scheme for valley pseudospin manipulation should also extend to the recently discovered quantum-confined states of excitons in TMDC layers [29][30][31][32][33] . For these localized excitonic states, the valley pseudospin degree of freedom is expected to be well preserved 34 , but their lifetimes are far longer than for the free excitons examined in this work.…”
mentioning
confidence: 97%
“…Our scheme for valley pseudospin manipulation should also extend to the recently discovered quantum-confined states of excitons in TMDC layers [29][30][31][32][33] . For these localized excitonic states, the valley pseudospin degree of freedom is expected to be well preserved 34 , but their lifetimes are far longer than for the free excitons examined in this work.…”
mentioning
confidence: 97%
“…[6][7][8][9] In particular, defect-derived excitonic states have recently received much attention for their applications in single-photon emitters. To date, several groups have reported that atomic-layer TMDCs show photoluminescence (PL) from optically active defects at low temperature (4 ∼ 90 K).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Local strain gradients which occur at the edges are considered to modulate the electronic states of the localized excitons, 2, 9-11 resulting in spatially and spectrally isolated single photon emission. This means that strain engineering is an effective approach to obtain spatially and spectrally isolated quantum emitters in two-dimensional (2D) semiconductors.…”
mentioning
confidence: 99%
“…Here, we present an effective method to give rise to single photon emission lines in monolayer WSe 2 and provide experimental evidence to show that the deep level defects should be responsible for the emission of single photon lines. The results are based on the application of hydrostatic pressure technique in the low temperature photoluminescence (PL) measurement of monolayer WSe 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation